A Model of Unsteady Seepage Flow in Low-permeable Coalbed with Moving Boundary in Consideration of Wellbore Storage and Skin Effect. (2015) - Liu, Wenchao; Liu, Yuewu; Niu, Congcong; Han, Guofeng; Wan, Yizhao
Abstract: The non-Darcy seepage flow in low-permeable coalbed and the strong adsorption of coalbed methane are the two key characteristics in the process of coalbed methane development in China. Based on these concerns, a model of unsteady seepage flow in low-permeable coalbed with moving boundary is built, which incorporates both the existence of threshold pressure gradient and the stable and unstable adsorption of coalbed methane simultaneously. Moreover, the effects of wellbore storage and skin effect are both considered, which can be incorporated in the inner boundary conditions. Due to the strong nonlinearity and complexity of the model with moving boundary, a verified numerical method of spatial coordinate transformation based fully implicit finite difference method is adopted to obtain its numerical solutions. By using these numerical solutions, the effects of the dimensionless coefficient of wellbore storage, the skin factor, the dimensionless threshold pressure gradient and the dimensionless coefficient of unstable desorption on the formation pressure distribution are analyzed, and some significant conclusions are obtained.